HUBUNGAN MINAT SISWA BEKERJA DI DUNIA INDUSTRI DENGAN HASIL BELAJAR MATA PELAJARAN GAMBAR KONSTRUKSI BANGUNAN SISWA KELAS XI TEKNIK GAMBAR BANGUNAN DI SMK NEGERI 1 PADANG - 547-555 , Randhi Ardian (Universitas Negeri Padang, 2015)
Abstract This research is a quantitative correlation of research which purpose to find out how much the relationship of variables between the student’s interest to work in the Industry with Learning Outcomes of Building Construction Drawing Course. The population in this research were all students of class XI Building Drawing Engineering Department at SMK Negeri 1 Padang 2014/2015 school year, as many as to 57 people. The sampling technique used is total sampling which entire class XI student of Building Design Engineering Department as many as 57 students. The research instrument used was a questionnaire. Students learning outcomes in Building Construction Drawing Course are below minimum completeness criteria as much as 66.67% on TGB A class XI and as much as 56.67% in class XI TGB B. Based on the analysis of research result, a correlation coefficient rcount of 0.234 in in the low category and significance value of ρ (0.04) is smaller than α (alpha) (0.05) or ρ = 0.04 < α = 0.05 so that H0 is rejected. This means that there is a significant relationship between students’ insterest to work in the industry with the learning outcomes of Building Construction Drawing Course of class XI student of Building Drawing Engineering Department at SMK Negeri 1 Padang. Keywords: Interests, Work, Industry, Learning Outcomes, Building Construction Design